Photocurable reactive adhesive film based on (meth)acrylate-functionalized polyurethane

CN122996137APending Publication Date: 2026-10-27TESA SE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480090107.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-02-07
Filing Date
2024-12-17
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0007]所有前述自由基聚合反应性胶带的缺点可能是它们必须含有丙烯酸酯单体或甲基丙烯酸酯单体的事实

Benefits of technology

[0152]根据本发明的反应性胶粘剂膜的另外的优点在于,反应性中心密度可经由聚氨酯中的丙烯酸酯官能化的和/或甲基丙烯酸酯官能化的二醇和/或多元醇的比例来控制,而不必改变配制物中的流动性组分的比例。因此,增加或减少反应性中心的比例对尚未固化的根据本发明的反应性胶粘剂膜的粘弹性的影响小于经由通常为液体的反应性单体的比例进行控制时的情况。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention relates to photocurable reactive pressure-sensitive adhesive films based on acrylate- and / or methacrylate-functionalized polyurethanes, the curing of which is initiated by blue LED light or UV LED light, which cures sufficiently slowly so that, if necessary, for example when non-transparent substrates are to be bonded, the joining of the parts to be bonded can be carried out within a certain time interval after initiation, and the curing continues even in the dark after bonding. With the adhesive films according to the invention, high bond strengths can be achieved. The adhesive films comprise (a) at least one acrylate- and / or methacrylate-functionalized polyurethane, (b) at least one initiator, in particular a free-radical initiator, (c) at least one photo-oxidation-reduction catalyst. Reactive monomers are not necessary.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to photocurable reactive pressure-sensitive adhesive films, methods for preparing reactive adhesive films, the use of adhesive films for bonding various materials such as plastics, metals, glass and / or ceramics, and a composite body comprising at least two adhesive surfaces connected to each other by a cured reactive pressure-sensitive adhesive film. Background Technology

[0002] Reactive adhesive films whose curing can be initiated by light, particularly UV light, are known. The reactive chemicals or substances used to cure such adhesive films are based on reactive acrylic monomers that undergo free radical polymerization when initiated by (UV) light. In this respect, the curing reaction is initiated by a photoinitiator, which decomposes in a photolysis reaction after absorbing (UV) light and thus forms a reactive substance that initiates free radical polymerization. A disadvantage here is the rapid nature of the curing reaction, especially when bonding opaque substrates. Once the reaction has begun, there is usually not enough time to bond the parts to be bonded. Therefore, such adhesive films are only suitable for bonding (UV) transparent substrates, since irradiation can then be applied through the parts after bonding. Another disadvantage of this type of adhesive film is that polymerization cannot continue as a dark reaction.

[0003] DE 1020 19209513 A1 describes reactive adhesive films based on acrylic monomers that do not exhibit the disadvantages described in the prior art. The disadvantages described here have proven to be insufficient heat and moisture resistance for many applications.

[0004] EP 4 159 775 B1 proposed a reactive adhesive film that improves resistance to heat and moisture, and can be used to obtain very high so-called structural bond strength.

[0005] EP 3 390 553 A1 proposes a method in which an adhesive tape made of two layers A and B (which react with each other and are separated by a barrier layer) is reacted and thus cured by means of a laser, wherein the barrier layer is removed by the action of the laser. The disadvantage here is that a laser is required.

[0006] EP 3 126 402 A1 discloses a method in which a free radical polymerization reaction is initiated by plasma treatment of an adhesive film containing a substance reactive in free radical polymerization and other catalytically active substances. This method produces a sufficiently slow curing rate. A drawback is that plasma devices suitable for achieving good adhesive strength are not yet widely available on the market. Furthermore, the achievable adhesive strength results depend on parameters such as humidity, which are difficult to influence in some areas.

[0007] A major drawback of all the aforementioned free radical polymerizable reactive tapes is the fact that they must contain acrylate or methacrylate monomers. A disadvantage in this case is that most acrylate or methacrylate monomers have a strong and unpleasant odor. Furthermore, many acrylate or methacrylate monomers have relatively high vapor pressures and can therefore escape prematurely from the uncured tape. The number of acrylate or methacrylate monomers that do not possess these unfavorable properties, or at least do not have very pronounced properties, is small, which significantly limits the design possibilities for formulations used in this type of tape. Summary of the Invention

[0008] Therefore, the object of this invention is to provide a photocurable reactive pressure-sensitive adhesive film that functions even without the use of acrylate monomers or methacrylate monomers. "Functional" here means that the adhesive film must be able to cure, wherein the adhesive film must be able to establish cohesive strength and sufficient adhesion to the substrate to be bonded, so that adhesion can be achieved. Curing should be ignited by blue LED light or UV LED light. The adhesive film should cure slowly enough to allow for bonding of the parts to be bonded within a certain time interval after initiation, such that even opaque parts can be bonded. After initiation and bonding of the parts, the adhesive film should continue to cure even in the dark.

[0009] Achievement of the goal

[0010] This objective is achieved by a photocurable reactive pressure-sensitive adhesive film according to the main claim, comprising: (a) at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane, (b) at least one initiator, and (c) at least one photoredox catalyst. Detailed Implementation

[0011] All details in this specification apply to adhesive films according to the invention, to tapes according to the invention, to methods for preparing adhesive films according to the invention, to composites according to the invention, and to uses of adhesive films or tapes according to the invention.

[0012] This invention also covers all features that form the subject matter of any dependent patent claim. Furthermore, this invention covers combinations of individual features with each other, as well as combinations of different levels of preference. Thus, for example, this invention covers combinations of a first feature designated as "preferred" and a second feature designated as "particularly preferred." This also covers subject matter having different levels of preference specified in the context of "implementation."

[0013] Acrylic-functionalized and / or methacrylate-functionalized polyurethanes

[0014] The reactive adhesive film according to the invention comprises (a) at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane.

[0015] The phrase "acrylate-functionalized and / or methacrylate-functionalized" means that polyurethanes can be functionalized with acrylates and methacrylates, or with both acrylates and methacrylates.

[0016] Preferably, the polyurethane (a) is functionalized with acrylate or methacrylate. Therefore, the reactive adhesive film according to the invention preferably comprises acrylate-functionalized or methacrylate-functionalized polyurethane.

[0017] Unless otherwise stated, this applies to all embodiments within the context of this invention.

[0018] Specifically, the polyurethane is a film-forming polymer of the reactive adhesive film according to the invention. Therefore, it imparts its film form to the reactive adhesive film according to the invention. The acrylate-functionalized and / or methacrylate-functionalized polyurethane remains pressure-sensitive prior to light curing. According to Römpp (Römpp Online 2013, document identifier RD-08-00162), this type of viscoelastic adhesive film is defined as pressure-sensitive when the set, dried film is permanently tacky and remains adhesive at room temperature. Adhesive bonding is achieved immediately on almost any substrate by slight contact pressure. Slight contact pressure here means a contact pressure greater than 0 bar, applied for a duration greater than 0 seconds. Generally, knowledge of the subject of pressure-sensitive adhesion forms part of the prior art and is fully presented, for example, in "Sata's Handbook of PressureSensitive Adhesive Technology, Third Edition, (1999)".

[0019] Furthermore, acrylate-functionalized and / or methacrylate-functionalized polyurethanes are reactive, derived from acrylate and / or methacrylate functionalization. It is known that acrylate and methacrylate groups can undergo free radical reactions, which can be initiated, for example, by free radical initiators.

[0020] In a preferred embodiment, the acrylate-functionalized and / or methacrylate-functionalized polyurethane is a chemical reaction product of: a1) at least one diol and / or polyol, a2) at least one acrylate-functionalized and / or methacrylate-functionalized diol and / or polyol, and a3) at least one diisocyanate and / or polyisocyanate.

[0021] In principle, all known dihydroxy-functionalized or polyhydroxy-functionalized substances can be considered as diols / polyols, particularly all polyester diols / polyols, including all polycaprolactone diols / polyols, all polyester carbonate diols / polyols, all polyether diols / polyols, and all polybutadiene diols / polyols, as well as substances derived therefrom or derivatives thereof. Furthermore, so-called chain extenders and / or crosslinking agents may also be considered, which herein refer to dihydroxy-functionalized or polyfunctionalized substances that are not polymeric compounds.

[0022] The polyester diol / polyol that can be used according to the present invention is a polyester having terminally bonded hydroxyl groups.

[0023] Polyester diols contain two terminally bonded hydroxyl groups and are therefore bifunctional. The number of terminally bonded hydroxyl groups in polyester polyols is not well-defined. Two or more hydroxyl groups may be present per molecule. In this document, the term polyester polyol should be understood to mean those containing more than two hydroxyl groups per molecule. Polyester diols / polyols usable according to the invention are generally obtained by the condensation polymerization of diols / polyols and dicarboxylic acids / polycarboxylic acids, or, in the case of polycaprolactone polyols, by ring-opening polymerization of ε-caprolactone and bifunctional or polyfunctional initiator molecules.

[0024] Polyester carbonate diols are dihydroxy-functionalized polyesters whose molecular chains also contain at least one carbonate group. They can be obtained, for example, through the polymerization of diols, dicarboxylic acids, and dimethyl carbonate (DMC) or diphenyl carbonate (DPC). The number of terminally bonded hydroxyl groups in polyester carbonate polyols is not well defined. Two or more hydroxyl groups may be present per molecule. In this document, the term polyester carbonate polyol should be understood to mean those containing more than two hydroxyl groups per molecule.

[0025] The polyether glycols / polyols usable according to the present invention are polyethers containing terminally bonded hydroxyl groups. Polyether glycols have two terminally bonded hydroxyl groups and are therefore bifunctional. The number of terminally bonded hydroxyl groups in polyether polyols is not specifically defined. Two or more hydroxyl groups may be present per molecule. In this document, the term polyether polyol should be understood to mean those containing more than two hydroxyl groups per molecule. The polyether glycols / polyols usable according to the present invention are prepared primarily from ethylene oxide, propylene oxide, or tetrahydrofuran by ring-opening polymerization or copolymerization using initiator molecules that determine functionality.

[0026] Polybutadiene glycol is a dihydroxy-functionalized polybutadiene prepared from butadiene by anionic polymerization. A known example of a commercially available product is the Krasol® type from Cray Valley.

[0027] Polybutadiene polyols may have two or more hydroxyl groups per molecule. In this document, the term polybutadiene polyol should be understood to refer to those containing more than two hydroxyl groups per molecule. They are prepared from butadiene through free radical polymerization. A known example of a commercially available product is the Poly bd® type from Cray Valley.

[0028] Examples of chain extenders include 1,2-ethylene glycol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, 2,3-butanediol, propylene glycol, dipropylene glycol, 1,4-cyclohexanediol, or 2-ethyl-1,3-hexanediol.

[0029] Examples of crosslinking agents are glycerol, trimethylolpropane, or 1,2,4-butanetriol.

[0030] According to a particularly advantageous embodiment of the invention, a1) at least one diol and / or polyol is selected from polyester diol, polyester polyol, polyester carbonate diol and polyester carbonate polyol, wherein polyester diol and / or polyester carbonate diol is particularly preferred.

[0031] According to a preferred embodiment of the invention, a2) at least one acrylate-functionalized and / or methacrylate-functionalized diol and / or acrylate-functionalized and / or methacrylate-functionalized polyol is a diol or a polyol (meth)acrylate alkyl ester, wherein the alkyl residue is linear or branched, and the alkyl residue contains 3 to 20, preferably 3 to 10, more preferably 3 to 6, and particularly, as an example, 3 or 5 carbon atoms.

[0032] The term “diol (meth)acrylate alkyl ester” should be understood to mean (meth)acrylate alkyl ester compounds containing two hydroxyl groups on an alkyl residue.

[0033] The term “polyol (meth)acrylate alkyl ester” should be understood to mean (meth)acrylate alkyl ester compounds containing more than two hydroxyl groups, such as three hydroxyl groups, on an alkyl residue.

[0034] The object of the present invention is achieved in a particularly favorable manner using such acrylate-functionalized and / or methacrylate-functionalized diols and / or acrylate-functionalized and / or methacrylate-functionalized polyols.

[0035] According to a particularly preferred embodiment of the present invention, the at least one acrylate-functionalized and / or methacrylate-functionalized diol and / or acrylate-functionalized and / or methacrylate-functionalized polyol mentioned in a2) is selected from 2,3-dihydroxypropyl acrylate (CAS No.: 10095-20-2), 2,3-dihydroxypropyl methacrylate (CAS No.: 5919-74-4), 1,3-dihydroxy-2-propyl acrylate (CAS No.: 119051-91-1), and 3-hydroxy-2,3-bis(hydroxymethyl)propyl acrylate (CAS No.: 55919-77-2).

[0036] More particularly preferably, a2) is at least one acrylate-functionalized and / or methacrylate-functionalized diol, wherein this is even more particularly preferably selected from 2,3-dihydroxypropyl acrylate and 2,3-dihydroxypropyl methacrylate.

[0037] In this regard, a photocurable reactive pressure-sensitive adhesive film is particularly preferred, wherein the at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane comprises the following chemical reaction products: a1) at least one diol and / or polyol, a2) 2,3-dihydroxypropyl acrylate and / or 2,3-dihydroxypropyl methacrylate, and a3) at least one diisocyanate and / or polyisocyanate.

[0038] The diisocyanates and / or polyisocyanates that can be used according to the present invention (a3) ​​are all known aliphatic and / or aromatic diisocyanates and / or polyisocyanates. Diisocyanates have two isocyanate groups per molecule, meaning they are bifunctional. Polyisocyanates have two or more isocyanate groups per molecule. In this document, the term polyisocyanate should be understood to mean those containing more than two isocyanate groups per molecule.

[0039] Examples of suitable diisocyanates and / or polyisocyanates are 1-isocyanatomethyl-3-isocyanato-1,5,5-trimethylcyclohexane (isophorone diisocyanate, IPDI), hexane-1,6-diisocyanate (hexamethylene diisocyanate, HDI), dicyclohexylmethane-4,4'-diisocyanate (H12MDI), toluene diisocyanate, diphenylmethane-4,4'-diisocyanate and / or m-tetramethylxylene diisocyanate (TMXDI), mixtures of said isocyanates or isocyanates chemically derived therefrom, such as dimer, trimer or polymeric types, which, for example, contain urea, ureidone or isocyanurate groups.

[0040] According to an advantageous embodiment, hexane-1,6-diisocyanate (hexamethylene diisocyanate, HDI) is used as a3).

[0041] To accelerate the reaction of diols / polyols with diisocyanates / polyisocyanates, one or more catalysts known to those skilled in the art can be used, such as tertiary amines, bismuth, or organotin compounds, to name just a few.

[0042] Highly advantageously, catalysts containing bismuth and carbon can be used, preferably bismuth carboxylate or bismuth carboxylate derivatives, especially bismuth trinedecanoate, CAS No.: 34364-26-6.

[0043] The concentration of the catalyst is adjusted according to the diol / polyol and diisocyanate / polyisocyanate used. Typically, it is between 0.01 wt% and 0.5 wt% of the polyurethane to be prepared.

[0044] Acrylic-functionalized or methacrylate-functionalized polyurethanes are preferably thermoplastic. Therefore, it is preferable to use bifunctional starting materials, namely diols and diisocyanates.

[0045] Triols are particularly suitable polyols, with higher polyols preferably avoided.

[0046] This applies to diols or polyols in groups a1) and a2).

[0047] When using triols from groups a1) and a2), care should be taken to ensure that gelation does not occur during the preparation of the polyurethane; that is, the degree of branching should not be too high relative to the length of the resulting polymer chains to avoid crosslinking during polyurethane preparation. The degree of branching should be adjusted to prevent the formation of crosslinked structures. To exclude crosslinked structures, the so-called gel point must not be exceeded. As is known to those skilled in the art, the theoretical gel point can be calculated using the gel point equation from PJ Flory or a formula derived from the Flory equation to estimate the NCO / OH gelation ratio in the polyurethane formation reaction from the diol and triol with the diisocyanate.

[0048] The derived formula is as follows: .

[0049] In this formula, the term diol-OH should be understood as referring to the total number of hydroxyl groups derived from diols and involved in the polyurethane formation reaction. This also includes chain extenders and acrylate-functionalized and / or methacrylate-functionalized diols. The term triol-OH should be understood as referring to the total number of hydroxyl groups bonded to triols and involved in the polyurethane formation reaction. This also includes crosslinking agents and acrylate-functionalized and / or methacrylate-functionalized triols.

[0050] In this respect, the NCO / OH ratio is preferably 0.5 to 1.

[0051] Number-average hydroxyl functionality should be understood as the average number of hydroxyl groups per molecule of a polymeric diol, such as a polyester diol, or a polymeric polyol, such as a polyester polyol. In this document, it should be understood as the number-average mean molecular weight of the corresponding diol or polyol, calculated according to the following formula: f= M n [g / mol] x HN [mmol OH / kg] / 10 6 , Where f is the number-mean hydroxyl functionality. M n HN represents the number-average molecular weight of the corresponding diol or polyol in [g / mol], and HN represents the hydroxyl value of the diol or polyol in [mmol OH / kg].

[0052] The hydroxyl value is a measure of the hydroxyl content in a diol or polyol.

[0053] The hydroxyl value was determined according to DIN 53240. In this method, the hydroxyl value (HN) is given in units of [mg KOH / g]. It corresponds to the amount of KOH, in [mg], which is equivalent to the amount of acetic acid bonded during the acetylation of 1 g of diol or polyol. For the purpose of simplifying formulation calculations, the hydroxyl values ​​in this document are converted to the unit [mmol OH / kg].

[0054] This is done using the following formula: HN [mmol OH / kg] = HN [mg KOH / g] x1000 / 56.1.

[0055] In this respect, 56.1 is the molar mass of KOH.

[0056] If the NCO / OH gelation ratio is reached or exceeded, the formation of cross-linked structures, i.e., the onset of gelation, must be expected. The equation derived from the Flory equation only provides an approximate indication of the NCO / OH ratio (above its actual gelation initiation), however, it is usually sufficient in practice.

[0057] When polyisocyanates with an isocyanate functionality of 3 are used together in the preparation of polyurethanes, similar considerations apply to prevent gelation. Therefore, the simultaneous use of triols and triisocyanates should also be avoided. For this reason, functionalities exceeding three should also be avoided.

[0058] To achieve pressure-sensitive adhesion, the NCO / OH ratio is preferably adjusted in such a way that even when only diols and diisocyanates are used, a slightly insufficient number of NCO groups are employed. In this case, the preferred NCO / OH ratio is in the range of 0.9 to 1.0, particularly preferably 0.9 to 0.99. If a trifunctional substance is also used, the desired NCO / OH ratio can be determined by the aforementioned formula. The NCO / OH ratio should be understood as the ratio of the total number of isocyanate groups involved in the polyurethane forming reaction to the total number of hydroxyl groups involved in the polyurethane forming reaction, i.e., the molar ratio of isocyanate groups to hydroxyl groups, regardless of whether the molecules of the corresponding substances react completely or only partially.

[0059] Furthermore, to obtain pressure-sensitive adhesive properties, it is preferable to select at least one diol and / or polyol with a number-average molecular weight M in such a manner as a1) n The concentration is such that it is between 400 g / mol (inclusive) and 6000 g / mol (inclusive), preferably between 1000 g / mol (inclusive) and 4000 g / mol (inclusive).

[0060] Furthermore, it is preferable to select the ratio of the number of hydroxyl groups derived from at least one diol and / or polyol derived from a1) to the number of hydroxyl groups derived from at least one acrylate-functionalized and / or methacrylate-functionalized diol or polyol in such a way that the ratio of the corresponding hydroxyl groups is between 95:5 and 5:95, preferably between 80:20 and 20:80.

[0061] The chemical reaction that forms polyurethane can be carried out in a solvent-free environment (i.e., in a melt), in an organic solvent, or in an aqueous dispersion. In the latter two cases, the polyurethane is dissolved in an organic solvent or dispersed in water. To enable better dispersion of polyurethane in water, dimethylolpropionic acid or a similar substance can be used, as is known in the art.

[0062] As is also known in the art, the reaction for constructing the corresponding prepolymer can be readily carried out in such a manner that only the OH groups react while the carboxyl functional groups remain uninvolved.

[0063] Polyurethane and its preparation are generally familiar to those skilled in the art.

[0064] Initiators, especially free radical initiators

[0065] The adhesive film according to the invention comprises (b) at least one initiator.

[0066] As used herein, the term initiator, particularly free radical initiator or free radical forming substance, refers to a compound that can initiate polymerization or crosslinking reactions of adhesive films. However, initiators, particularly free radical initiators, participate in the reaction process to a very small extent and therefore do not contribute to any arbitrary properties that determine the adhesiveness of polymer fractions.

[0067] In this invention, at least one initiator, particularly a free radical initiator, is added to the reactive adhesive film according to the invention. The initiator is selected in such a way that it does not initiate the reaction of the mixture with acrylate-functionalized and / or methacrylate-functionalized polyurethanes in temperatures up to 90°C, even when the mixture is irradiated with UV or blue light. This applies as long as no photoredox catalyst or other activating substance is added to the mixture. The initiator, particularly the free radical initiator, is explicitly not a photoinitiator. This also applies to the use of more than one initiator, particularly a free radical initiator: again, none of the compounds cited are photoinitiators.

[0068] Free radical initiators are preferred. Therefore, in a preferred embodiment, the photocurable reactive pressure-sensitive adhesive film according to the invention comprises at least one free radical initiator as an initiator (b). Any free radical initiator known in the prior art can be used. Preferred free radical initiators are peroxides, particularly hydroperoxides.

[0069] In a particularly preferred embodiment of the invention, the free radical initiator is an organic peroxide, such as peroxycarboxylic acid and hydroperoxide.

[0070] Hydroperoxides are particularly preferred, especially diisopropylbenzene hydroperoxide (CAS No. 26762-93-6). Diisopropylbenzene hydroperoxide is preferably used in the form of a 50% by weight solution of diisopropylbenzene, available under the trade name Peroxan® IHP-50 (Pergan GmbH, Bocholt, Germany). α,α-dimethylbenzyl hydroperoxide, also known as cumene hydroperoxide (CAS No. 80-15-9), can also be used, for example. Furthermore, p-menthane hydroperoxide (CAS No. 26762-92-5), tert-amyl hydroperoxide (CAS No. 3425-61-4), tert-butyl hydroperoxide (CAS No. 75-91-2), or 1,1,3,3-tetramethylbutyl hydroperoxide (CAS No. 5809-08-5) can also be used.

[0071] The proportion of the initiator, particularly the free radical initiator, is preferably in the range of 0.1 to 10% by weight, preferably 0.2 to 5% by weight, relative to the total mixture of components of the reactive adhesive film according to the invention.

[0072] In the context of this invention, the total mixture of components of the reactive adhesive film according to the invention represents the total amount of (a) acrylate-functionalized and / or methacrylate-functionalized polyurethane, (b) initiator, (c) photoredox catalyst, and (d) optional other optional components used, which together amount to 100% by weight. Solvents or water are used only in preparation and are not considered in this respect as part of the total mixture of components forming the reactive adhesive film according to the invention. This also applies to solvents that may already be present in commercially available raw materials.

[0073] Photo-oxidation-reduction catalyst

[0074] The adhesive film according to the invention comprises (c) at least one photo-oxidation-reduction catalyst.

[0075] As used herein, the term photoredox catalyst refers to a photosensitive or UV-sensitive compound that, when excited by light or UV light, mediates electron transfer between chemical compounds that would otherwise react more slowly or not at all. Compared to photoinitiators, photoredox catalysts, when irradiated with light or UV light, do not decompose into reactive decomposition products but only transform into excited states, which typically have relatively long lifetimes and from which redox processes can be initiated or mediated. Photoredox catalysts preferably do not initiate the reaction of a mixture with at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane at temperatures up to 90°C, even when the mixture is irradiated with UV or blue light. This applies as long as no free radical initiator or other initiating substance is added to the mixture. Therefore, a photoredox catalyst is not an initiator. When irradiated with UV or blue light, it only activates the initiator, which then initiates the polymerization or crosslinking reaction. This also applies if two or more photoredox catalysts are used. Here, photoredox catalysts are also not initiators.

[0076] Photo-redox catalysts known to those skilled in the art can be used as photo-redox catalysts. Many of the most commonly used photo-redox catalysts are polypyridyl transition metal complexes, such as ruthenium and iridium complexes, for example, Ru(bpm)3. 2+ (e.g., tris(2,2'-bipyridine)ruthenium(II) chloride), Ru(bpz)3 2+ (e.g., tris(2,2'-bipyrazine)ruthenium bis(hexafluorophosphate)), Ru(bpy)3 2+ Ru(phen)3 2+ (For example, ruthenium(II) chloride trichlorotris(1,10-phenanthroline) chloride), lr[dF(CF3)ppy]2(dtbbpy) + (e.g. [4,4'- pair(1,1-Dimethylethyl)-2,2'-Bipyridine- N1,N1 ']bis[3,5-difluoro-2-[5-(trifluoromethyl)-2-pyridyl- N [Phenyl-C]iridium(III)hexafluorophosphate), lr(ppy)3, lr(ppy)2(dtbbpy) + (e.g., [Ir(dtbbpy)(ppy)2] [PF6]), lr(Fppy)3 or fac -lr(ppy)3 (fac-tris(2-phenylpyridine)iridium(III)). However, copper complexes, such as Cu(dap), can also be used. 2+ (e.g., 2,9-bis(4-methoxyphenyl)-1,10-phenanthroline copper chloride).

[0077] According to a preferred embodiment of the present invention, at least one photoredox catalyst is a transition metal complex having ruthenium as a central atom and bipyridine or a mono- or poly-substituted bipyridine derivative as a ligand. According to another preferred embodiment of the present invention, at least one photoredox catalyst is a transition metal complex having iridium as a central atom and phenylpyridine or a mono- or poly-substituted phenylpyridine derivative as a ligand.

[0078] According to a particularly preferred embodiment of the present invention, the photo-oxidation-reduction catalyst is selected from: i. [tris(2,2'-bipyridyl)ruthenium(II)] 2+ [Ru(bpy)3] 2+ - Equation (Ia):

[0079] ii. Tris[2-(2,4-difluorophenyl)pyridine]iridium(III), Ir(Fppy)3; CAS No.: 387859-70-3-Formula (Ib):

[0080] iii. Tris(2-phenylpyridinato)iridium(III), Ir(ppy)3; CAS No.: 94928-86-6-Formula (Ic): .

[0081] The preferred counterion of the cation having formula (1a) is chloride. The corresponding commercially available products contain water of crystallization.

[0082] Therefore, a particularly preferred embodiment of the photo-redox catalyst having formula (Ia) is tris(2,2'-bipyridyl)ruthenium(II) chloride hexahydrate (CAS No.: 50525-27-4), which is available from CHEMOS GmbH & Co. KG (Altdorf, Germany, http: / / www.chemos.de).

[0083] Photo-redox catalysts with formula (1c) are also available from CHEMOS GmbH & Co. KG.

[0084] Photo-redox catalysts of formula (Ib) are available from Strem (Europe) (Bischheim, France, http: / / www.strem.com).

[0085] The proportion of the photo-oxidation-reduction catalyst is preferably in the range of up to 1% by weight, preferably up to 0.5% by weight, wherein the minimum amount is advantageously 0.01% by weight, referring respectively to the total mixture of the components of the reactive adhesive film according to the invention.

[0086] Preferably, the photocurable reactive pressure-sensitive adhesive film according to the invention does not contain any other activating or initiating components or components that affect the activation and initiation processes other than those cited in this document, and in particular, does not contain photoinitiators.

[0087] Other components of reactive adhesive films

[0088] The reactive adhesive film according to the invention may optionally contain other additives and / or auxiliary substances known in the art. The proportions of these other additives and / or auxiliary substances may range from 0 to 60% by weight, preferably 0 to 40% by weight, and particularly preferably 0 to 20% by weight, relative to the total mixture of components of the reactive adhesive film according to the invention. Examples of other additives and / or auxiliary substances include fillers, colorants, nucleating agents, rheology modifiers (e.g., ignited silica), foaming agents, adhesive strengthening additives (adhesion promoters, particularly silanes and tackifier resins), compounding agents, plasticizers, and / or anti-aging, light, and UV agents, for example in the form of primary and secondary antioxidants. Additives may also perform several functions simultaneously.

[0089] Other components of the reactive adhesive film according to the present invention may also be reactive monomers or oligomers.

[0090] According to a preferred embodiment of the invention, the reactive adhesive film according to the invention further contains reactive monomers, particularly (meth)acrylate monomers. This allows the properties of the adhesive film to be adapted particularly well to specific requirements with a wide range of design flexibility. Advantageously in this respect, the monomers are selected such that they have the lowest possible vapor pressure, thereby still achieving the objectives of the invention in the best possible manner.

[0091] According to another preferred embodiment of the invention, the reactive adhesive film according to the invention is free of additional reactive monomers, and therefore free of reactive monomers. In the context of the invention, the expression "free of" encompasses a certain amount of residual as impurities, such that the amount of reactive monomers in these embodiments is preferably 0 to 0.01% by weight, but particularly 0% by weight.

[0092] These embodiments have enabled the objectives of the invention to be achieved in a particularly satisfactory manner.

[0093] Other film-forming substances may also constitute components of the reactive adhesive film according to the invention, as well as polymers prepared from monomers containing N-vinyl compounds, as described in EP 4 159 775 B1.

[0094] reactive adhesive film

[0095] The photocurable reactive pressure-sensitive adhesive film according to the invention is in the form of a film. As used herein, the term "adhesive film" (or adhesive layer, adhesive foil) is intended to cover the application (application) of the photocurable reactive adhesive mixture, which is provided wholly or partially as described below. Thus, for example, applying the adhesive in spots that do not completely cover the surface of the substrate to be bonded can also result in permanent adhesion within the meaning of this invention.

[0096] In a preferred embodiment, the photocurable reactive pressure-sensitive adhesive film according to the present invention comprises: (a) 10 to 99% by weight of at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane, and (b) at least one initiator, from 0.1 to 10.0% by weight, and (c) At least one photo-oxidation-reduction catalyst, up to 1.0% by weight. And optionally, (d) 0 to 60% by weight of other additives and / or auxiliary substances, wherein the total amount of the components is equal to 100 by weight.

[0097] The following are even better options: (a) 50 to 99% by weight of at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane, and (b) 0.5 to 8.0% by weight of at least one initiator, and (c) At least one photo-oxidation-reduction catalyst, up to 0.5% by weight. (d) 0 to 40% by weight of other additives and / or auxiliary substances, wherein the total amount of the components is equal to 100 by weight.

[0098] The following are the optimal choices: (a) 80 to 99% by weight of at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane. (b) 1.0 to 5.0% by weight of at least one initiator, (c) at least one photo-oxidation-reduction catalyst, up to 0.2% by weight; (d) 0% to about 20% by weight of other additives, wherein the total amount of the components is equal to 100% by weight.

[0099] In a particularly preferred embodiment of the invention, the photocurable reactive pressure-sensitive adhesive film according to the invention comprises a mixture of the following components: (a) Acrylate-functionalized and / or methacrylate-functionalized polyurethanes, prepared by reacting: a1) having an approximate number-average molecular weight M of 2000 g / mol. n The polyester diol or polyester carbonate diol having an approximate number-average molecular weight of 2000 g / mol, and a2) 2,3-dihydroxypropyl acrylate (CAS No.: 10095-20-2) or 2,3-dihydroxypropyl methacrylate (CAS No.: 5919-74-4), with a3) diisocyanate, preferably hexamethylene diisocyanate or isophorone diisocyanate or dicyclohexylmethane-4,4'-diisocyanate, at an NCO / OH ratio between 0.9 and 1.0. (b) diisopropylbenzene hydroperoxide, and (c) Tris(2,2'-bipyridyl)ruthenium(II) chloride hexahydrate.

[0100] According to a particularly preferred embodiment of the invention, the components comprise 80 to 99% by weight of acrylate-functionalized and / or methacrylate-functionalized polyurethane, (b) 1.0 to 5.0% by weight of dicumylbenzene hydroperoxide, and (c) up to 0.2% by weight of tris(2,2'-bipyridyl)ruthenium(II) chloride hexahydrate, relative to the total mixture of components of the reactive adhesive film according to the invention.

[0101] Typically, the reactive adhesive film according to the invention has a layer thickness in the range of 20 to 200 µm, preferably 30 to 100 µm, more preferably 40 to 60 µm, and particularly preferably 50 µm (measured using a commercially available thickness gauge, such as the DM 2000 from Wolf Messtechnik GmbH). To produce a greater layer thickness, it may be advantageous to laminate several layers of adhesive film together.

[0102] Furthermore, the reactive adhesive film according to the invention is characterized in that it has pressure-sensitive adhesive properties before being cured by light, wherein "pressure-sensitive adhesive" is as defined above for polyurethane.

[0103] Furthermore, the photocurable reactive pressure-sensitive adhesive film according to the present invention may include additional films, foils, layers, carriers, adhesive films, pressure-sensitive adhesive films, release paper and / or release liner.

[0104] Suitable carrier materials are known to those skilled in the art. For example, foil (polyester, PET, PE, PP, BOPP, PVC, polyimide), nonwovens, foams, fabrics, and / or fabric foils can be used as permanent carriers. Temporary carriers should be provided with a release layer, which is typically prepared from a silicone release lacquer or a fluorinated release lacquer, or has polyolefin properties (HDPE, LDPE).

[0105] According to a preferred embodiment of the invention, the adhesive film according to the invention is used as a single-layer film, which is also referred to by those skilled in the art as transfer tape.

[0106] Here, the tape also advantageously includes release paper and / or release liner for easy storage.

[0107] According to another preferred embodiment of the invention, the reactive adhesive film (A1) according to the invention, together with another reactive adhesive film (A2) according to the invention and a film, foil, layer or carrier (B), forms a multilayer reactive pressure-sensitive tape.

[0108] Therefore, the reactive pressure-sensitive tapes of these embodiments comprise the following layers: - A photocurable reactive pressure-sensitive adhesive film (A1) according to the present invention; and - A further photocurable reactive pressure-sensitive adhesive film (A2) according to the invention; and - A film, foil, layer or carrier (B) arranged flat between two reactive pressure-sensitive adhesive films (A1) and (A2).

[0109] This results in three layers of reactive pressure-sensitive tape in the layer arrangement (A1 / B / A2).

[0110] According to a preferred embodiment of the present invention, the tape is composed of layers A1 / B / A2.

[0111] However, the tape may also contain additional layers, such as the photocurable reactive pressure-sensitive adhesive film of the present invention or other adhesive layers or additional carrier layers.

[0112] Preferably, the film, foil, layer, or carrier (B) is a polyethylene foil, polypropylene foil, or polyester foil, and more particularly preferably a polyester foil etched with trichloroacetic acid.

[0113] Preferably, the film, foil, layer, or carrier (B) disposed between the two reactive pressure-sensitive adhesive films (A1) and (A2) according to the invention is a polyethylene foil, polypropylene foil, or polyester foil, more particularly preferably a polyester foil etched with trichloroacetic acid. As an example, such an etched polyester foil with a thickness of 12 μm is available under the trade name Kemafoil® HPH 100 12µ (Coveme SPA, San Lazzaro di Savena, Italy).

[0114] The tape also conveniently includes release paper and / or release liner for easy storage.

[0115] Preparation method of reactive adhesive film

[0116] The method according to the present invention includes the following steps: i. The preparation of the at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane (A) in one or more solvents or water, or solvent-free, ii. Dissolving and / or finely dispersing components (a), (b), and (c) in one or more solvents or water, or solvent-free methods, wherein UV or visible light of the wavelengths that excite the respective photoredox catalysts is excluded. iii. Mixed, dissolved, or finely dispersed components, iv. Coat a film, foil, layer, carrier, adhesive film, pressure-sensitive adhesive film, preferably release paper or release liner, with the mixture of the dissolved or finely dispersed components from step iii. v. Evaporate the solvent or water, provided that the preceding steps were not performed in the absence of solvent or water. vi. Optionally, to wind a reactive adhesive film into a roll.

[0117] The preparation of at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane (a) according to step i. has been described above and is carried out in one or more solvents or in water, or in a solvent-free manner.

[0118] In step ii., the components are dissolved or finely dispersed in one or more solvents and / or water. Suitable solvents are known in the art, with solvents in which at least one component has good solubility preferably used. Acetone and methyl ethyl ketone (MEK) are particularly preferred.

[0119] As used herein, the term "component" encompasses: (a) at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane, (b) at least one initiator, (c) at least one photo-redox catalyst, and (d) other optional components as described above, where applicable.

[0120] The preparation of the photocurable reactive pressure-sensitive adhesive film according to the present invention is carried out no later than step ii with the addition of the photo-oxidation-reduction catalyst, wherein UV or visible light, especially violet and blue light, of the wavelengths that excite the corresponding photo-oxidation-reduction catalyst are excluded.

[0121] Typically, and in the context of this invention, these are preferably wavelengths less than 500 nm, particularly 300 to 500 nm. Exclusion can typically be achieved using commercially available warm light lamps and by covering a normal light source having a UV component and / or violet and blue components in its wavelength spectrum with commercially available UV-blocking warm foil.

[0122] Then, in step iii, the dissolved or finely dispersed components are mixed using standard mixing equipment. Where applicable, the components are dissolved, finely dispersed, and mixed simultaneously.

[0123] Subsequently, in step iv., a mixture of dissolved, finely dispersed components is coated onto a film, foil, layer, carrier, adhesive film, pressure-sensitive adhesive film, preferably a release liner or release paper. The coating is applied using standard techniques known in the art.

[0124] In step v., after coating, the solvent or water is removed by evaporation, provided that the aforementioned steps are not performed in the absence of solvent or water.

[0125] Depending on the solvent used, this is preferably carried out in a temperature range of 60 to 80°C.

[0126] If applicable, in a separate step vi., the reactive adhesive film may be wound into a roll.

[0127] For storage purposes, the reactive adhesive film according to the invention is preferably covered with a release liner or release paper.

[0128] The preparation of the three-layer reactive pressure-sensitive tape according to the invention is carried out by: preparing the first (A1) and second (A2) reactive pressure-sensitive adhesive films according to the invention, wherein the two reactive pressure-sensitive adhesive films according to the invention are brought into contact with a film, foil, layer or carrier (B), optionally during lamination or by direct coating, such that the result is a three-layer reactive pressure-sensitive tape having a layer arrangement (A1 / B / A2).

[0129] base

[0130] Various plastics, metals, glass, and / or ceramics constitute substrates suitable for bonding with the reactive adhesive film according to the invention. The substrates to be bonded may be the same or different. They may be transparent or opaque.

[0131] The reactive adhesive film according to the invention is preferably used for bonding plastics, metals, and glass. Particularly preferred are polycarbonates, polyamides, anodized aluminum, steel (e.g., stainless steel), and glass (especially surface-treated glass).

[0132] The metal substrate to be bonded can generally be made of all common metals and metal alloys. Metals such as aluminum, stainless steel, steel, magnesium, zinc, nickel, brass, copper, titanium, ferrous metals, and alloys are preferred. The parts to be bonded can also be made of different metals.

[0133] Examples of suitable plastic substrates include polycarbonate (PC), polyamide (PA), acrylonitrile-butadiene-styrene copolymer (ABS), ABS / PC blends, PMMA, glass fiber reinforced polyamide, polyvinyl chloride, polyvinyl fluoride, cellulose acetate, cyclic olefin copolymers, liquid crystal polymers (LCP), polylactide, polyetherketone, polyetherimide, polyethersulfone, polymethacryloylmethylimide, polymethylpentene, polyphenylene ether, polyphenylene sulfide, polyphthalamide, polyurethane, polyvinyl acetate, styrene-acrylonitrile copolymer, polyacrylate or polymethacrylate, polyoxymethylene, acrylate-styrene-acrylonitrile copolymer, polyethylene, polystyrene, polypropylene and / or polyester, such as polybutylene terephthalate (PBT) and / or polyethylene terephthalate (PET).

[0134] The substrate can be painted, printed, vapor coated, or sputtered.

[0135] Regarding their shape, the substrates to be bonded are preferably planar or two-dimensionally curved. However, depending on the degree of curvature, three-dimensionally curved substrates can also be bonded using the reactive adhesive film according to the invention. The substrates to be bonded can also achieve a wide variety of functions, such as housings, viewing windows, reinforcing elements, etc.

[0136] Where appropriate, it may be necessary to pretreat the surfaces of the substrates to be bonded using physical, chemical, and / or physicochemical methods. For example, applying a primer or adhesion promoter composition is advantageous. Similarly, corona, plasma, or flame pretreatment may be advantageous.

[0137] Advantageously, the reactive adhesive film according to the invention can be used to bond components in the electronics industry, particularly smartphone components and tablet components such as touchscreens. Preferred bonding applications include mounting camera lenses, bonding flexible displays in wearable devices (e.g., fitness trackers and smartwatches), attaching / mounting antennas or backlight units in smartphones or tablets, FPC (flexible printed circuit) mounting or film lamination, and mounting speaker drivers.

[0138] Adhesion method

[0139] The reactive adhesive film according to the invention can be used in a method for bonding two substrates, such as substrate 1 (e.g., polycarbonate) to another substrate 2 (e.g., metal), to obtain a composite.

[0140] The method for bonding two substrates according to the present invention preferably includes the following steps: (xi) Provides a first substrate S1; (xii) Provide a second substrate S2; (xiii) Arrange the reactive adhesive film according to the invention or the reactive pressure-sensitive tape according to the invention on the substrate S1; (xiv) Before or after the adhesive film or tape is placed on the substrate S1: the adhesive film or tape is irradiated with UV or blue light to form an irradiated adhesive film or tape and to cause curing. (xv) Arrange two substrates S1 and S2 such that they are bonded to each other by an irradiated adhesive film or an irradiated adhesive tape; and (xvi) The following arrangement: to cure the irradiated adhesive film or irradiated tape by irradiation.

[0141] Alternatively, the irradiation in step (xiv) may also be performed after the arrangement or connection (xv) of the two substrates has occurred, particularly in cases where at least one substrate is transparent to the activation radiation.

[0142] Complex

[0143] Furthermore, according to the present invention, a composite comprising at least two adhesive surfaces is provided, wherein the two adhesive surfaces are connected by a cured reactive adhesive film according to the present invention or by a cured reactive pressure-sensitive tape as defined above.

[0144] Product Nature

[0145] The reactive adhesive film according to the invention exhibits superior product properties that are even unexpected to those skilled in the art. Depending on the photo-redox catalyst used, the adhesive film can be cured with commercially available UV or blue LED lamps (e.g., wavelengths of 365 nm, 385 nm, 395 nm, 405 nm, 450 nm, and 460 nm). Surprisingly, it has been found that UV or blue LED lamps are equally suitable in many cases. Commercially available mercury vapor UV lamps are also suitable.

[0146] Examples of suitable LED light sources for curing the reactive adhesive film according to the invention include the following products from Hönle (Dr. Hönle AG, Gilching, Germany, https: / / www.hoenle.de / ): a) LED Spot 100 HP IC 365 nm (UV LED), b) LED Spot 100 HP IC 460 nm (blue light LED).

[0147] The LED Cube 100 IC, also from Hönle, is designed for illumination chambers specifically for these light sources. The appropriate dose is approximately 10 to 80 J / cm². 2 Within this range. Therefore, typically 30% to 90% power output is selected on the aforementioned device. The irradiation time is selected between 10 and 60 seconds. The distance between the light source and the reactive adhesive film according to the invention is approximately 2 to 10 cm. When using other devices with different outputs, significant deviations from the stated guidelines are expected.

[0148] After irradiation, the adhesive film does not cure immediately. It remains tacky initially. Depending on the photo-redox catalyst used and the exact adhesive formulation, bonding or joining of the substrate is possible over a period of at least five minutes, sometimes up to 30 minutes. In other words, the adhesive film according to the invention has an open time of at least 5 minutes after irradiation and thus initiation of curing. The adhesive film according to the invention fully cures within a period of approximately 24 hours after the irradiation ends. Curing occurs independently of light and therefore also in darkness. Therefore, the adhesive film / adhesive foil according to the invention can also be used to bond opaque substrates.

[0149] High adhesive strength can be obtained using the reactive adhesive film according to the invention. In push-out tests, values ​​greater than 2.0 MPa can be obtained when bonding polycarbonate test specimens (PC-PC: polycarbonate to polycarbonate); in preferred embodiments, values ​​even greater than 6.0 MPa can be obtained (see examples). Bonding of steel, anodized aluminum, and polyamide also results in acceptable adhesive strengths, significantly higher than those of non-reactive pressure-sensitive adhesives. Good values ​​are also obtained in mechanical impact tests. Furthermore, the adhesive film according to the invention exhibits excellent impact properties.

[0150] As shown in the embodiments, the reactive adhesive film according to the invention also exhibits good stability during storage. Furthermore, post-curing via a crystallization process does not occur in the cured adhesive because cross-linked polyurethanes do not crystallize, unlike many non-crosslinked polyurethanes. Therefore, the adhesive strength achieved after curing is stable in this respect.

[0151] The fact that high adhesive strength can be obtained with the reactive adhesive film according to the invention is surprising, since the adhesive film does not contain any reactive monomers. This means that the flowability component is missing, which those skilled in the art would consider essential for the development of adhesion. Given the absence of reactive monomers, the significant build-up of cohesion (which becomes apparent when compared with the comparative examples) is also surprising. Those skilled in the art would predict that the reactive adhesive film according to the invention would crosslink upon irradiation, but the significant increase in cohesive strength and the simultaneous development of adhesion (both essential for high adhesive strength) are surprising.

[0152] Another advantage of the reactive adhesive film according to the invention is that the density of reactive centers can be controlled by the ratio of acrylate-functionalized and / or methacrylate-functionalized diols and / or polyols in the polyurethane, without having to change the proportion of flowable components in the formulation. Therefore, increasing or decreasing the proportion of reactive centers has less effect on the viscoelasticity of the uncured reactive adhesive film according to the invention than when controlled by the proportion of reactive monomers, which are typically liquids.

[0153] Experimental Section

[0154] The following examples are used to illustrate the present invention, but should not be construed as limiting the scope of protection.

[0155] Table 1 lists the raw materials and materials used to prepare the photocurable reactive pressure-sensitive adhesive film according to the present invention, the three-layer photocurable reactive pressure-sensitive adhesive tape according to the present invention, and the comparative examples, each having a trade name, manufacturer or supplier information, and technical data related to the present invention.

[0156] Table 1

[0157] The determination of the hydroxyl value of polyester carbonate diol and polyester diol is performed according to DIN 53240. According to this method, the hydroxyl value (HN) is given in units of [mg KOH / g]. It corresponds to the amount of KOH in [mg], which is equivalent to the amount of acetic acid bonded during the acetylation of 1 g of polyol. To simplify formulation (composition) calculations, the hydroxyl values ​​in this document are converted to units of [mmolOH / kg].

[0158] This is done using the following formula: HN [mmol OH / kg] = HN [mg KOH / g] x 1000 / 56.1. In this respect, 56.1 is the molecular weight of KOH.

[0159] Taking into account the corresponding functionality, the OH and NCO values ​​of the remaining diol and diisocyanate are calculated directly from the corresponding molecular weight.

[0160] In addition, commercially available silicone release liner (release foil) was used. Acetone (CAS No.: 67-64-1) was used as the solvent in the examples and comparative examples.

[0161] Preparation of acrylate-functionalized or methacrylate-functionalized polyurethane solutions

[0162] The corresponding acrylate-functionalized or methacrylate-functionalized polyurethanes were prepared as follows: First, polyester (carbonate) diol was weighed and stirred under vacuum at 70°C for 2 hours in a standard heated and evacuated laboratory mixer (e.g., from PC Laborsystem). The diol was then transferred to a screw-cap flask, and after brief cooling, solvent (acetone), 2,3-dihydroxypropyl (meth)acrylate, and catalyst (Coscat® 83) were added, and the mixture was stirred for 30 minutes without vacuum and heating using a standard laboratory stirrer. Diisocyanate was then added and stirred until homogeneous. The chemical reaction mixture was stirred for 90 minutes, with small amounts of escaping solvent continuously added. To complete the reaction, the sealed screw-cap flask was stored in a warming cabinet at 40°C for 7 days.

[0163] Prepare the following polyurethane solutions: PU-1: NCO / OH ratio: 0.93

[0164] PU-2: NCO / OH ratio: 0.97

[0165] PU-3: NCO / OH ratio: 0.93

[0166] PU-4: NCO / OH ratio: 0.97

[0167] PU-5: NCO / OH ratio: 0.93

[0168] PU-6: NCO / OH ratio: 0.97

[0169] PU-7: NCO / OH ratio: 0.93

[0170] PU-8: NCO / OH ratio: 0.97

[0171] PU-9 comparison: NCO / OH ratio: 0.97

[0172] Preparation of aqueous solutions of photo-oxidation-reduction catalysts

[0173] A photo-oxidation-reduction catalyst was used as a 5% by weight aqueous solution to prepare the adhesive film according to the present invention. This solution was obtained as follows: Aqueous solution of tris(2,2'-bipyridyl)ruthenium(II) chloride hexahydrate Under yellow light, 5 g of tris(2,2'-bipyridyl)ruthenium(II) chloride hexahydrate and 95 g of completely softened water were weighed into a brown screw-cap flask. The screw-cap flask was sealed. The tris(2,2'-bipyridyl)ruthenium(II) chloride hexahydrate was completely dissolved by rolling the screw-cap flask on a rolling table for 8 hours.

[0174] Example 1

[0175] Preparation of the reactive adhesive film according to the present invention and the three-layer reactive tape according to the present invention

[0176] Weigh 95.78 g of 70% polyurethane solution PU-1 and 3.40 g of Peroxan® IHP-50 (containing 50% diisopropylbenzene hydroperoxide) into a brown screw-cap flask and mix for 15 minutes at medium speed (500-1000 rpm) using a commercially available laboratory stirrer.

[0177] All other operations were performed under yellow light. An LT35WT5EQ / Yellow Special fluorescent lamp from NARVA Lichtquellen GmbH (NARVALichtquellen GmbH + Co. KG, Brand-Erbisdorf, Germany, www.narva-bel.de) was selected for the yellow ceiling lighting, blocking wavelengths below 500 nm. To cover any residual light from other light sources, Metolight SFLY-5 yellow foil (ASMETEC GmbH, Kirchheimbolanden, Germany, www.asmetec.de) was selected, filtering out wavelengths below 470 nm.

[0178] Add 0.82 g of 5% by weight aqueous solution of tris(2,2'-bipyridyl)ruthenium(II) chloride hexahydrate and mix at medium speed for 5 minutes using a laboratory stirrer. Then, mix the mixture on a commercial rolling stand for 24 hours.

[0179] Using a commercial laboratory coating station equipped with a doctor blade (e.g., from SMO, SondermaschinenOschersleben GmbH, Oschersleben, Germany), the resulting homogeneous mixture was successively spread three times onto a silicone-coated polyester foil (release liner) to obtain three films. The solvent was then evaporated for 15 minutes at 60°C in a circulating air drying oven. The gap width during spreading was varied. It was adjusted twice to obtain a 50 μm thick film after solvent evaporation each time. In the third spreading experiment, the gap width was adjusted to obtain a 100 μm thick film after solvent evaporation. The resulting 100 μm thick photocurable reactive pressure-sensitive adhesive film was covered with a second silicone-coated polyester foil (release liner). Subsequently, circular die-cut pieces (roundels) with a diameter of 21 mm were punched out and stored in opaque plastic containers until testing. Testing was conducted two weeks after die-cutting preparation and again after storage at 23°C and 50% relative humidity for six months.

[0180] To prepare the three-layer reactive tape according to the invention, the first layer of two 50 μm thick reactive adhesive films was laminated onto a Kemafoil® HPH 100 12µm polyester foil etched with trichloroacetic acid. This was performed at room temperature, for example, under light pressure using a smooth lamination roller (pressure roller). The second 50 μm thick reactive adhesive film was then laminated onto the other side of the trichloroacetic acid-etched polyester foil in the same manner. The resulting three-layer photocurable reactive tape was then covered on both sides with correspondingly siliconized polyester foil (release liner). Subsequently, annular die-cut pieces with an outer diameter of 18 mm and an inner diameter of 13 mm were punched from it. These were also stored in opaque plastic containers until testing. Again, testing was performed two weeks after die-cutting and six months after storing the die-cut pieces at 23°C and 50% relative humidity.

[0181] The percentage composition by initial weight of the solution / mixture used to prepare the photocurable reactive pressure-sensitive adhesive film and the percentage composition of the photocurable reactive pressure-sensitive adhesive film itself are listed in the following two tables: Example 1: Percentage composition of solution / mixture used to prepare reactive adhesive films

[0182] Example 1, Percentage Composition of Reactive Adhesive Film

[0183] The reactive adhesive film according to the invention, as well as the three-layer reactive tape according to the invention in other embodiments and comparative embodiments, were prepared in a manner similar to that of Example 1.

[0184] Example 2: Percentage composition of solution / mixture used to prepare reactive adhesive films

[0185] Example 2, Percentage Composition of Reactive Adhesive Film

[0186] Example 3: Percentage composition of solvent / mixture used to prepare reactive adhesive films

[0187] Example 3, Percentage Composition of Reactive Adhesive Film

[0188] Example 4: Percentage composition of solvent / mixture used to prepare reactive adhesive films

[0189] Example 4, Percentage Composition of Reactive Adhesive Film

[0190] Example 5: Percentage composition of solvent / mixture used to prepare reactive adhesive films.

[0191] Example 5, Percentage Composition of Reactive Adhesive Film

[0192] Example 6: Percentage composition of solvent / mixture used to prepare reactive adhesive films

[0193] Example 6, Percentage Composition of Reactive Adhesive Film

[0194] Example 7: Percentage composition of solvent / mixture used to prepare reactive adhesive films

[0195] Example 7, Percentage Composition of Reactive Adhesive Film

[0196] Example 8: Percentage composition of solvent / mixture used to prepare reactive adhesive films.

[0197] Example 8, Percentage Composition of Reactive Adhesive Film

[0198] Comparative Examples

[0199] Compared to Example 1, which corresponds to Example 4, except that no irradiation was performed.

[0200] Percentage composition of solution / mixture

[0201] Compared to Example 1, which corresponds to Example 4, except that no irradiation was performed.

[0202] Percentage composition of the membrane

[0203] Comparative Example 2, percentage composition of solution / mixture

[0204] Comparative Example 2, percentage composition of the membrane

[0205] Comparative Example 3, percentage composition of solution / mixture

[0206] Comparative Example 3, percentage composition of the membrane

[0207] Comparative Example 4, percentage composition of solution / mixture

[0208] Comparative Example 4, percentage composition of the membrane

[0209] Comparative Example 5, percentage composition of solution / mixture

[0210] Comparative Example 5, percentage composition of the membrane

[0211] Comparative Example 6, Percentage Composition of Solution / Mixture

[0212] Comparative Example 6, percentage composition of the membrane

[0213] Comparative Example 7, percentage composition of solution / mixture

[0214] Comparative Example 7, percentage composition of the membrane

[0215] Launch test and mechanical shock test

[0216] As the compressive load increases steadily, the push-out test allows for the determination of the adhesive strength of the double-sided adhesive product in the normal direction of the adhesive layer.

[0217] When the impact load is not damped, mechanical impact testing allows for the determination of the adhesive strength of double-sided adhesive products in the normal direction of the adhesive layer.

[0218] Test specimens for ejection testing and mechanical impact testing

[0219] A circular object with a diameter of 21 mm is used. A square perforated plate based on a side length of 40 mm is also used. The corresponding holes are centrally arranged in the middle. It is circular, and in each case the hole diameter is 9 mm. The circular object used is made of polycarbonate, anodized aluminum, and SUS steel. The square perforated plate used is made of polycarbonate, polyamide, anodized aluminum, and SUS steel.

[0220] In detail, the following test specimens are used: a) Round objects: - Plastic disc made of polycarbonate (PC), Makrolon 099, polished and burr-free, 21 × 3 mm - A disk made of anodized aluminum (Al), alloy 5005A, AlMg1, and anodized E6 EV1, 21 × 2 mm - A circular object made of steel grade VA1.4301 (equivalent to SUS 304), with laser-cut outer contours and mirror-polished side, measuring 21 x 2 mm. b) Square perforated plate: - A plastic test specimen made of polycarbonate (PC), manufactured by Makroform 099, 40x40x4 mm, with a hole in the center of the plastic, D=9 mm. - Plastic test specimens made of polyamide (PA), reinforced with glass fiber, product: PA6 granules, natural, 25% GF, Ultramid B3WG5, 40x40x4 mm plastic with a hole in the center, D=9 mm.

[0221] - A test specimen, 40x40x3 mm, prepared from aluminum (Al), alloy 5005A, AlMg1, and anodized E6 EV1, with a central hole in the aluminum portion, D=9 mm.

[0222] - Test specimens made of steel grade VA1.4301 (equivalent to SUS 304), with inner and outer contours laser-cut and surface mirror-polished, measuring 40x40x3 mm, and featuring a central hole with a diameter of 9 mm.

[0223] The plastic and aluminum test specimens were sourced from Rocholl GmbH (Eschelbronn, Germany, https: / / rocholl.eu / ). The steel test specimens were supplied by Classen GmbH (Rellingen, Germany, www.classen-laser.de / ).

[0224] Sample preparation for ejection and mechanical impact testing

[0225] The distinction is made between a single-layer photocurable reactive pressure-sensitive adhesive film according to the invention (which is supplied as a 100 μm thick circular die-cut piece (circular object)) and a three-layer reactive tape according to the invention (which consists of two 50 μm thick reactive films and a 12 μm thick polyester foil etched with trichloroacetic acid disposed between the two 50 μm thick reactive films, and which is supplied as a die-cut ring).

[0226] Pull the release liner of each die-cut part off from one side of the die-cut part.

[0227] Each die-cut part is placed centered in the middle of the circular test specimen.

[0228] The die-cut part then adheres to the circular test specimen.

[0229] Then remove the remaining release paper from the die-cut piece. Thus, the test specimen is now equipped with a single layer of reactive adhesive film (the specimen) and three layers of reactive tape (the ring).

[0230] Irradiation used for ejection tests and mechanical impact tests

[0231] In the first series of experiments, only UV LED light (365 nm) was used for irradiation, and in the second series of experiments, only blue LED light (460 nm) was used. The dosage was selected as follows: - LED Spot 100 HP IC 365 nm (UV-LED): 30.0 - 34.0 J / cm 2 - LED Spot 100 HP IC 460 nm (Blue LED): 50.0 - 55.0 J / cm 2 The dose of UV and blue LED light was measured using a UV meter from Hönle (Dr. Hönle AG, Gilching, Germany, https: / / www.hoenle.de / ), UV light (340-405 nm) with a UVA F0 surface sensor, and blue LED light (360-550 nm) with a VIS F1 surface sensor.

[0232] The time interval between the end of irradiation and the bonding of the test specimens was always between 1 and 2 minutes. Multiple checks were conducted, and it was found that even time intervals of at least 5 minutes or longer were possible without reducing adhesive strength.

[0233] Adhesive for ejection testing and mechanical impact testing

[0234] The corresponding open side of the die-cut test specimen circular object, equipped with an irradiated die-cut section, is positioned on a perforated plate such that the center of the circular object and the center of the hole in the perforated plate overlap each other. Subsequently, the composite material consisting of the square perforated plate, the irradiated die-cut section, and the test specimen circular object is compacted using a press from Howe Elektrotechnik eK (Glinde, Germany, https: / / howe-hamburg.de / ), held together by the pressure-sensitive properties of the die-cut section. The compaction parameters are: 3 bar, 30 seconds.

[0235] After compaction, the composite was stored in a standardized climate at 23°C and 50% relative humidity (rh) for 3 days. This resulted in a gradual curing reaction within the die-cut part and a gradual increase in adhesion between the die-cut part and the test specimen. This led to a gradual increase in bond strength over time. Push-out tests and mechanical impact tests (freshness values) were then performed.

[0236] To assess storage stability, un-irradiated and unbonded die-cut parts, with release liner on both sides, were stored in darkness for six months in a standard climate at 23°C and 50% relative humidity. The die-cut parts were then irradiated and bonded as described above. Push-out and mechanical impact tests were then performed.

[0237] The test specimens were bonded together in the following combination: PC round object against PC board PC round object against PA board The round object in Al resists the Al plate. The round steel object pressed against the steel plate The bonding surface is: - Circular die-cut parts (circular objects): 283 mm 2 (Considering the 9 mm hole in the board) - Circular die-cut part: 122 mm 2

[0238] Conduct rollout testing

[0239] The mandrel, clamped in the tensile testing machine, is pushed vertically through the hole in the perforated plate at a constant speed of 10 mm / min onto the circular test specimen (i.e., the normal vector parallel to the plane of the test specimen; centered on the center of the hole), until the adhesive bonds to separate to the point of a 50% pressure drop is recorded. The pressure applied immediately before the pressure drop is the maximum pressure P. maxThis value corresponds to the derived value [MPa] given in the table. All measurements were performed in a climate-controlled room at 23°C and 50% relative humidity (rh).

[0240] Conduct mechanical impact testing

[0241] The mechanical impact test is limited to the three-layer reactive tape according to the invention and is performed under blue light. The bonded test specimens are clamped in a sample holder with the composite horizontally oriented, with the circular object at the bottom and the square perforated plate at the top. The sample holder is then inserted centered into the receiver provided in the instrument used (“DuPont Impact Tester”, Cometech, TAIWAN, Model QC-641). The impact head is placed in the hole of the square perforated plate, such that the circularly rounded impact geometry with a 5 mm diameter is centered and flush with the bonded side of the circular object. A 307 g weight (slide plate) guided on two guide rods is dropped vertically from an initial height of 5 cm onto the composite of the prepared sample holder, the bonded test specimen, and the impact head (measurement conditions: 23°C, 50% relative humidity). The height (h) of the dropped weight is increased in 5 cm increments until the applied impact energy breaks the bond through the impact load and the circular object separates from the square perforated plate. In all cases where the adhesive bond was broken, even from a height of 5 cm, these measurements were repeated with a slide with a mass of 156 g. The energy at which the bond was broken corresponds to the impact energy values ​​given in the table. These impact energy values, also known as DuPont impact values, are calculated as follows: DuPont impact value [mJ / cm] 2 ] = 1000 (m(sled)[kg)) 9.81 [kg / m s 2 ] h[m]) / A(adhesive area)[cm 2 ]

[0242] Release test results and mechanical shock test results

[0243] For all embodiments (according to the present invention and comparative embodiments) and for all the properties of the measurements, the average of three separate measurements was determined.

[0244] Failure Mode : A = Adhesive; K = Cohesion; M = Mixture failure

[0245] Example 1

[0246] Launch test

[0247] Monolayer product (spherical object)

[0248] Launch test

[0249] Three-layer product (ring)

[0250] Impact test

[0251] Three-layer product (ring)

[0252] Example 2

[0253] Launch test

[0254] Monolayer product (spherical object)

[0255] Launch test

[0256] Three-layer product (ring)

[0257] Impact test

[0258] Three-layer product (ring)

[0259] Example 3

[0260] Launch test

[0261] Monolayer product (spherical object)

[0262] Launch test

[0263] Three-layer product (ring)

[0264] Impact test

[0265] Three-layer product (ring)

[0266] Example 4

[0267] Launch test

[0268] Monolayer product (spherical object)

[0269] Launch test

[0270] Three-layer product (ring)

[0271] Impact test

[0272] Three-layer product (ring)

[0273] Example 5

[0274] Launch test

[0275] Monolayer product (spherical object)

[0276] Launch test

[0277] Three-layer product (ring)

[0278] Impact test

[0279] Three-layer product (ring)

[0280] Example 6

[0281] Launch test

[0282] Monolayer product (spherical object)

[0283] Launch test

[0284] Three-layer product (ring)

[0285] Impact test

[0286] Three-layer product (ring)

[0287] Example 7

[0288] Launch test

[0289] Monolayer product (spherical object)

[0290] Launch test

[0291] Three-layer product (ring)

[0292] Impact test

[0293] Three-layer product (ring)

[0294] Example 8

[0295] Launch test

[0296] Monolayer product (spherical object)

[0297] Launch test

[0298] Three-layer product (ring)

[0299] Impact test

[0300] Three-layer product (ring)

[0301] Comparative Examples

[0302] Comparative Example 1

[0303] Launch test

[0304] Monolayer product (spherical object)

[0305] The product did not cure. After being bonded and stored in a standardized climate for the next 3 days, it remained unchanged and sticky.

[0306] Comparative Example 2

[0307] Launch test

[0308] Monolayer product (spherical object)

[0309] The product did not solidify. After being irradiated and stored in a standardized climate for the next 3 days, it remained unchanged and sticky.

[0310] Comparative Example 3

[0311] Launch test

[0312] Monolayer product (spherical object)

[0313] The product did not solidify. After being irradiated and stored in a standardized climate for the next 3 days, it remained unchanged and sticky.

[0314] Comparative Example 4

[0315] Launch test

[0316] Monolayer product (spherical object)

[0317] The product did not solidify. After being irradiated and stored in a standardized climate for the next 3 days, it remained unchanged and sticky.

[0318] Comparative Example 5

[0319] Launch test

[0320] Monolayer product (spherical object)

[0321] Upon irradiation with UV light, the product cures immediately, making it possible to avoid adhesion. Upon irradiation with blue light, the product does not cure. After irradiation and storage in a standard climate for the following 3 days, it remains unchanged and sticky.

[0322] Comparative Example 6

[0323] Launch Test: Single-layer product (circular object)

[0324] Upon irradiation with UV light, the product cures immediately, making it possible to avoid adhesion. Upon irradiation with blue light, the product does not cure. After irradiation and storage in a standard climate for the following 3 days, it remains unchanged and sticky.

[0325] Comparative Example 7

[0326] Launch Test: Single-layer product (circular object)

[0327] Upon irradiation with UV light, the product cures immediately, making it possible to avoid adhesion. Upon irradiation with blue light, the product does not cure. After irradiation and storage in a standard climate for the following 3 days, it remains unchanged and sticky.

[0328] Impact tests were also performed on the three-layer products (rings) from Comparative Examples 1 to 7. All descriptions similarly apply to the preparation of Comparative Examples 1 to 7. Results showed that no product solidification occurred in the comparative examples. After bonding and subsequent storage under standard climatic conditions for 3 days, the products remained unchanged and tacky.

[0329] None of the test samples in any comparative example reached 63 mJ / cm. 2 The minimum possible impact energy value, which can be measured in the testing apparatus used with a 156 g trolley weight (minimum drop height of 5 cm), is thus determined. Therefore, as a result of the impact test, <63 mJ / cm 2More precise values ​​are not possible in any comparative embodiment.

[0330] This applies to all test specimen substrates, namely PC / PC, PA / PC, Al / Al, and steel / steel.

[0331] Discussion of Results

[0332] The reactive adhesive film according to the invention can be cured using both UV LED light and blue LED light. After irradiation, it does not cure immediately but has an open time of at least 5 minutes. It continues to cure in the dark, making it suitable for bonding opaque substrates. High adhesive strength can be obtained with the reactive adhesive film according to the invention. This is particularly evident when bonding polycarbonate. However, adhesion to aluminum, polyamide (PA), and SUS steel also exhibits significantly higher adhesive strength than that of pressure-sensitive adhesives. Good values ​​are also obtained in mechanical impact tests, reflecting the high adhesive strength, especially with polycarbonate. As shown in the examples, the reactive adhesive film according to the invention also exhibits good storage stability.

[0333] The reactive adhesive film according to the invention represents a significant improvement over the prior art because it works even without reactive monomers, i.e., reactive monomers are not necessary to obtain adhesive strength significantly exceeding that it possesses in its uncured state (i.e., when it is in a tacky state before light exposure). This becomes particularly apparent when compared with Comparative Example 1.

[0334] This is surprising because the absence of reactive monomers implies a lack of flowability components, which those skilled in the art would consider essential for establishing adhesion. The significant accumulation of cohesion (which becomes apparent by comparison with comparative examples) is also surprising given the absence of reactive monomers. Those skilled in the art might predict that the reactive adhesive film according to the invention would crosslink upon irradiation, but the significant increase in cohesive strength and the simultaneous accumulation of adhesion (both essential for high adhesive strength) are surprising.

[0335] Comparative Examples 2, 3, and 4 show that the (meth)acrylate functional group, as well as the initiator and photo-redox catalyst, are essential components of the reactive adhesive film according to the present invention. As shown in Comparative Examples 5, 6, and 7, the commercially available photoinitiator used as the substance initiating the curing reaction is not a substitute, neither a replacement for the initiator nor a replacement for the photo-redox catalyst.

Claims

1. A photocurable reactive pressure-sensitive adhesive film, comprising: (a) At least one acrylate-functionalized and / or methacrylate-functionalized polyurethane, (b) at least one initiator, and (c) At least one photo-oxidation-reduction catalyst.

2. The photocurable reactive pressure-sensitive adhesive film according to claim 1, characterized in that, The at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane comprises the following chemical reaction products: a1) at least one diol and / or polyol, a2) at least one acrylate-functionalized and / or methacrylate-functionalized diol and / or acrylate-functionalized and / or methacrylate-functionalized polyol, and a3) at least one diisocyanate and / or polyisocyanate.

3. The photocurable reactive pressure-sensitive adhesive film according to claim 2, characterized in that, a2) The at least one acrylate-functionalized and / or methacrylate-functionalized diol and / or acrylate-functionalized and / or methacrylate-functionalized polyol is a diol or polyol (meth)acrylate alkyl ester, wherein the alkyl residue is linear or branched, and the alkyl residue contains 3 to 20, preferably 3 to 10, more preferably 3 to 6, and particularly, as an example, 3 or 5 carbon atoms.

4. The photocurable reactive pressure-sensitive adhesive film according to claim 3, characterized in that, a2) The at least one acrylate-functionalized and / or methacrylate-functionalized diol and / or acrylate-functionalized and / or methacrylate-functionalized polyol is selected from 2,3-dihydroxypropyl acrylate, 2,3-dihydroxypropyl methacrylate, 1,3-dihydroxy-2-propyl acrylate, and 3-hydroxy-2,3-bis(hydroxymethyl)propyl acrylate, wherein it is preferably selected from acrylate-functionalized and / or methacrylate-functionalized diols and particularly preferably selected from 2,3-dihydroxypropyl acrylate and 2,3-dihydroxypropyl methacrylate.

5. The photocurable reactive pressure-sensitive adhesive film according to any one of the preceding claims, characterized in that, (a) The at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane is a thermoplastic polyurethane.

6. The photocurable reactive pressure-sensitive adhesive film according to any one of the preceding claims, characterized in that, The at least one photo-oxidation-reduction catalyst (c) comprises: Ruthenium as the central atom and bipyridine or mono- or poly-substituted bipyridine derivatives as ligands, or Iridium is used as the central atom and phenylpyridine or mono- or poly-substituted phenylpyridine derivatives are used as ligands.

7. The photocurable reactive pressure-sensitive adhesive film according to any one of the preceding claims, characterized in that, The at least one photoredox catalyst (c) comprises [tris(2,2'-bipyridyl)ruthenium(III)] 2+ Tris[2-(2,4-difluorophenyl)pyridine]iridium(III) or tris(2-phenylpyridine)iridium(III).

8. The photocurable reactive pressure-sensitive adhesive film according to any one of the preceding claims, comprising: (a) 10 to 99% by weight of at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane, (b) 0.1 to 10.0% by weight of at least one initiator, (c) At least one photo-oxidation-reduction catalyst, up to 1.0% by weight.

9. The photocurable reactive pressure-sensitive adhesive film according to claim 8, comprising: (a) 50 to 99% by weight of at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane. (b) 0.5 to 8.0% by weight of at least one initiator, (c) At least one photo-oxidation-reduction catalyst, up to 0.5% by weight.

10. The photocurable reactive pressure-sensitive adhesive film according to any one of the preceding claims, comprising additional films, foils, layers, carriers, adhesive films, pressure-sensitive adhesive films, release paper and / or release liner.

11. A photocurable reactive pressure-sensitive tape comprising the following layers: - The photocurable reactive pressure-sensitive adhesive film (A1) according to any one of claims 1 to 10; and - The additional reactive pressure-sensitive adhesive film (A2) according to any one of claims 1 to 10; and - A film, foil, layer or carrier (B) arranged flat between two reactive pressure-sensitive adhesive films (A1) and (A2).

12. A method for preparing a photocurable reactive pressure-sensitive adhesive film according to any one of claims 1 to 10, characterized in that, The method includes the following steps: vii. The preparation of at least one acrylate-functionalized and / or methacrylate-functionalized polyurethane (a) in one or more solvents or water, or solvent-free, viii. Dissolving and / or finely dispersing the components (a), at least one initiator (b), and at least one photo-redox catalyst (c) in one or more solvents or water, or solvent-free, wherein UV or visible light of the wavelength that excites the respective photo-redox catalyst is excluded. ix. Mixed, dissolved, or finely dispersed components. x. Coat a film, foil, layer, carrier, adhesive film, pressure-sensitive adhesive film, preferably release paper or release liner, with the mixture of the dissolved or finely dispersed components from step iii. xi. Evaporate the solvent or water, provided that the preceding steps were not performed in the absence of solvent or water. xii. Optionally, the reactive adhesive film is wound into a roll.

13. Use of the photocurable reactive pressure-sensitive adhesive film according to any one of claims 1 to 10 or the reactive pressure-sensitive tape according to claim 11 for producing adhesion on materials selected from plastics, metals, glass and / or ceramics.

14. A composite comprising at least two adhesive surfaces joined together by a cured reactive pressure-sensitive adhesive film according to any one of claims 1 to 10 or by a cured reactive pressure-sensitive tape according to claim 11.

Citation Information

Patent Citations

  • Cover for clarifiers

    CA80159A

  • UV-curing reactive adhesive

    DE102019209513A1

  • Photo-setting reactive adhesive film

    EP4159775B1